Analisis Kinerja Dinas Kesehatan Kabupaten Karawang dalam Penanggulangan Hiv/Aids di Kalangan Pelajar dan Mahasiswa - Thia Amelia; Haura Attahara; Gugun Gumilar (Peneliti.net, 2021)
This study discusses the performance analysis of the Karawang District Health Office in dealing with HIV/AIDS among students. The analytical study uses the theory of Robin and Judge Analysis of performance, with five dimensions, namely quality, quantity, cooperation, initiative and responsibility. The method used is descriptive qualitative with data collection through interviews, observation and documentation. The results of the study show that the Karawang Office has not been optimal in the quality and quantity sector due to an increase in the number of HIV/AIDS positives in Karawang in the last three years. While the sectors that have been assessed as optimal are initiative, collaboration and responsibility, this is because the Karawang Health Office is able to make good use of the external potential of the institution to realize solutions and actualization in HIV/AIDS prevention among students and students of Karawang Regency